SUBTITUTION OF MILLET FLOUR ON BREAD PIZZA DOUGH AS AN EFFORT TO REDUCE THE USE OF WHEAT FLOUR - Siti Hamidah, Muhamad Zuhdi Zulfikar (Prosiding Pendidikan Teknik Boga Busana, 2020)
Wheat import levels from year to year has increased so that efforts should be made to reduce imports of wheat from a simple thing that is exploiting the potential of local plants such as millet were used as flour and used for substitution in the manufacture of basic bread pizza. The study produced the data level of public acceptance by large-scale test is limited to the value of 0.646, which means product development significantly different with product reference on the instrument taste, then the instrument lowest test score comparison is on the texture of 0,036 suspected because the texture of millet flour used has the texture which is similar to wheat flour so that when mixed the two are not too change the texture. At the level of public acceptance test the overall scale-free instrument to get an average high of 3.55 it is quite high and it can be concluded that the product of this development can be accepted by society. Contained nutrients known to be highest in carbohydrates as much as 46.43% it is clear because the manufacture is derived from cereal crops which are a source of carbohydrates. Keywords: millet, bread, substitution, reduction, flour